Capture of Sulphur Dioxide by Hydroxyl Ammonium Ionic Liquid-DBU Mixtures - Qu, Guangfei; Jian, Ronglong; Zhang, Jun; Li, Jiangna; Ning, Ping (Asian Journal of Chemistry, 2014)
Three hydroxyl ammonium ionic liquids containing the alcoholic hydroxy group were synthesized that mixed with 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) to form integrated sorption systems with the mole ratio of 1:1. At ambient temperature and atmospheric pressure, the absorption of SO2 by integrated ionic liquid-DBU systems was investigated. The saturated absorption mole ratio of SO2/ILs was 0.30, 0.50 and 0.66, respectively. And that of SO2/ILs-DBU was 2.63, 2.83 and 2.96, respectively. The net increase in the saturated absorption mole ratio of three mixed absorption systems was close to 2.3 after deducting the SO2 saturated absorption capacity of pure ionic liquids. The results indicated that SO2 was absorbed fastly and efficiently by the mixed systems and the absorption could be completed in 0.5 h. In addition, the mixed systems had a strong regenerative ability. It’s absorption capacity and rate were hardly changed after four SO2 absorption-desorption cycle experiments.